2000
DOI: 10.1007/s004380000306
|View full text |Cite
|
Sign up to set email alerts
|

A gene cluster from Streptomyces galilaeus involved in glycosylation of aclarubicin

Abstract: We have cloned and characterized a gene cluster for anthracycline biosynthesis from Streptomyces galilaeus. This cluster, 15-kb long, includes eight genes involved in the deoxyhexose biosynthesis pathway, a gene for a glycosyltransferase and one for an activator, as well as two genes involved in aglycone biosynthesis. Gene disruption targeted to the activator gene blocked production of aclacinomycins in S. galilaeus. Plasmid pSgs4, containing genes for a glycosyltransferase (aknS), an aminomethylase (aknX), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 26 publications
1
29
0
4
Order By: Relevance
“…Coclustered with the deoxysugar biosynthesis gene locus were genes predicted for aglycone biosynthesis comprising an aromatic type II polyketide synthase (PKS). Further analysis of the gene set revealed its similarity to the aclacinomycin gene cluster from Streptomyces galileus (41,42). This enabled the classification of the target compound as a glycosylated anthracycline polyketide.…”
Section: A Ms-glycogenetic Code Connecting Microbial Gnp Chemotypes Andmentioning
confidence: 96%
“…Coclustered with the deoxysugar biosynthesis gene locus were genes predicted for aglycone biosynthesis comprising an aromatic type II polyketide synthase (PKS). Further analysis of the gene set revealed its similarity to the aclacinomycin gene cluster from Streptomyces galileus (41,42). This enabled the classification of the target compound as a glycosylated anthracycline polyketide.…”
Section: A Ms-glycogenetic Code Connecting Microbial Gnp Chemotypes Andmentioning
confidence: 96%
“…Although the gene clusters for both aclarubicin [77] and rhodomycin [96] have been partially sequenced, genes for these activities have not been assigned in either cluster. l-Oleandrose (77) is found in the macrolide antibiotic oleandomycin produced by Streptomyces antibioticus and in avermectin produced by Streptomyces avermitilis.…”
Section: 22mentioning
confidence: 99%
“…The encoded enzymes likely catalyze the corresponding steps in both sugar biosynthetic pathways. [62] The sugars l-nogalamine (52), [22] l-daunosamine (see 53), [76] and l-rhodosamine (see 54) [77] are found in the anthracycline antibiotics nogalamycin, daunorubicin, and aclarubicin, respectively. Their common precursor is 60, which undergoes 3,5-epimerization and stereospecific ketoreduction in each pathway.…”
Section: 22mentioning
confidence: 99%
“…This has prompted the study of this family of natural products to the level of their biosynthesis in order to develop new bioactive compounds by recombinant DNA technology (33). In particular, three anthracycline compounds have been studied so far: daunorubicin-doxorubicin (18), nogalamycin (59,56), and aclacinomycin (42,43). These studies have revealed the assembly of this type of compound by type II polyketide synthases (PKS) that consist of several discrete proteins carrying a set of iteratively used enzyme activities.…”
mentioning
confidence: 99%